2019
DOI: 10.1590/1983-40632019v4955074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen sources on fruit characteristics and seed physiological quality of Physalis angulata L.

Abstract: RESUMOangulata L., a naturally occurring species (Matos 2000), appears as an alternative for the region.P. angulata is a herbaceous plant of approximately 70 cm in height, popularly known in Brazil as mullaca, camapu and juá-de-capote (Freitas et al. 2006). Its fruit, a globose berry with numerous seeds, has a sweet and slightly acidic taste, with a high content of vitamins, phosphorus, iron, flavonoids and fibers (Velasquez et al. 2007, Rufato et al. 2008. Despite such a great potential, the species is not mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Sokri et al (2015) reported that improvement in fruit acidity contents of Malus domestica with NH4 + nutrition could be related to antagonistic effect of NH4 + with other cations. Tanan et al (2019) found that effect of NH4 + on fruit quality characteristics of Physalis angulata L. was associated with NH4 + ‐induced evolution of ethylene production which regulated the enzyme activities and fruit quality characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Sokri et al (2015) reported that improvement in fruit acidity contents of Malus domestica with NH4 + nutrition could be related to antagonistic effect of NH4 + with other cations. Tanan et al (2019) found that effect of NH4 + on fruit quality characteristics of Physalis angulata L. was associated with NH4 + ‐induced evolution of ethylene production which regulated the enzyme activities and fruit quality characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo comTanan et al (2019) as plantas apresentam resposta diferente em sua fisiologia e crescimento quando submetidas a diferentes fontes de nitrogênio. A preferência por N-NO3ou N-NH4 + depende da espécie e geralmente está ligada a fatores genéticos e ambientais.…”
unclassified